Explanation of Wisdom Based on Developmental Assets by Mediating Thriving (Developing a Causal Model) - shahriar moradi; rasool kord Noghabi; Abolghasem Yaghoobi; Khossro Rashid (پژوهش در نظام‌های آموزشی, 2018)
This research aimed to design a structural model for relationships between developmental assets with thriving and wisdom. For this aim, based on multistage-cluster sampling method, a sample of 668 students from Kermanshah universities was selected, and Wisdom Scale (3D-WS), Thriving Scale and Developmental Assets Profile (DAP) were completed by them. The data analyzed by using the path analysis method. The final model presented a particular pattern of relationship between the research variables, and could explain 0/23 of the variance of wisdom. The fitness indicators of the model showed the proper fit with the data (χ2/df=2.57, RMSEA=0/05, GFI=1/00, CFI=1/00,). Direct effects of internal assets on three dimensions of wisdom were confirmed, its indirect effects through thriving on cognitive and effective dimensions were significant but on the reflective dimension was not significant. Also, direct effect of external assets on reflective dimension was confirmed, but on the cognitive and effective dimensions didn''t confirm, and its indirect effects on cognitive and effective dimensions were significant but on reflective dimension was non-significant. Totally, internal assets more than external assets explained wisdom in the students.